Job Satisfaction on Primary Health Care Providers in the Rural Settings - M Arab; A Pourreza; F Akbari; N Ramesh; S Aghlmand (Tehran University of Medical Sciences, 2007)
"nBackground: Job satisfaction remains as an important concern for both employer and employee. The leaving of workplace and migration to city centers is one of the main results of Job dissatisfaction among the primary health care (PHC) providers in rural setting of Iran, Behvarzes. Determining the predictor's factors of the PHC providers' job dissatisfaction and providing appropriate strategies to address these factors can most likely improve their performance and diminish the problem."nMethods: Data were collected from 290 of the PHC providers worked full-time in Kurdistan rural health-house by a survey for identifying the individual, environmental, and work factors that influence job satisfaction."nResults: Only 17% of the participants' overall job satisfaction was high. Furthermore, the developed model presented statistically significant differences between job satisfaction and village population size, satellite villages covered, and distance between health-house and city center."nConclusion: It is expected that the finding of the study can help Iran health system policymakers and managers for planning and implementing effective policies in order to meet the PHC providers' needs and so improve quality of primary health care in the rural areas.